The Substantive Responsibility For Marine Pollution - احمد بسام; محمود لجين (Latakia University Journal - Economic and Legal Sciences Series, 2021)
The Research In This Regard Is Concerned With Pollution Of The Marine Environment, Which Is One Of The Vital Topics That Have Occupied The Attention Of The International Community In General and Coastal States In Particular, For Which The Conventions Aimed At Protecting The Marine Environment Were Concluded By Adopting The Rules Of Substantive Responsibility For Damages Resulting From Marine Pollution Accidents, Which Has Proved To Be The Legal Valve To Guarantee Individuals’ Rights And Facilitating Compensation For Damages Resulting From Pollution Of The Marine Environment In Cases Where Aggrieved Is Unable To Prove Fault In The Face Of Responsible. The Research aims To Briefing By Pillars Of Substantive Responsibility And The Implications Of establishing It In The Light Of International And Regional Conventions That Concern The Issue Of Pollution Of The Marine Environment. The Research concluded That The Implementation Of The Substantive Responsibility Rules will Achieve Greater Protection For Those Affected If The Period Of Limitation Extinguished For The Compensation Lawsuit Is Taken Into Account In The Interest Of Aggrieved, Especially Since Some Conventions Don’t Take Into Account That The Environmental Damage Is Slow To Emerge, Thus Losing The Right Of Aggrieved To Compensation Due To The Lapse Of Time.